The δ13C chemostratigraphy of Ordovician global stage stratotypes: geochemical data from the Floian and Sandbian GSSPs in Sweden. (2nd January 2020) - Bergström, Stig M.; Schmitz, Birger; Terfelt, Fredrik; Eriksson, Mats E.; Ahlberg, Per
ABSTRACT: The δ 13 C chemostratigraphy of five of the seven Ordovician global stages has been published previously but no such data have been available from the Floian GSSP and most of the Sandbian GSSP in Sweden. This lack of information has now been remedied by isotope data obtained from series of closely spaced shale samples collected from the Floian stratotype at Diabasbrottet in Västergötland and the Sandbian stratotype at Fågelsång in Scania. Although the bases of these stages cannot be precisely tied to levels of conspicuous δ 13 C excursions, that of the Floian Stage, which is marked by the appearance of the graptolite Tetragraptus approximatus, is between the closely spaced excursions named LTNICE and BFICE. The base of the Sandbian Stage, which is defined as the appearance level of the graptolite Nemagraptus gracilis, is just below a negative excursion previously known as the "Upper Kukruse Low", which is nowadays known as the LSNICE. The relations between chemostratigraphy and graptolite and conodont biostratigraphy in the Swedish GSSPs and some coeval key sections in Baltoscandia, China, and America are briefly discussed. It is concluded that the data at hand indicate that there is good regional agreement in these relations.